Development of android media in invertebrate learning - Nugroho , Bimo Aji; Soendjoto , Mochamad Arief; Zaini , Muhammad (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2023)
The development of android media for invertebrate material in biology lessons has not been carried out and needs to be optimized. The research aims to develop android media for invertebrate learning. This type of research is research and development using the Plomp and Nieveen development model, which is limited to the prototyping phase, and formative evaluation based on Tessmer which consists of self-evaluation, expert opinion, individual testing, small group testing, and field testing. The research subjects consisted of 3 experts and 30 students who had programmed the Invertebrates course for individual tests, small group tests, and field tests. The research instruments include validation sheets and essay-based tests. The acquired data was subjected to descriptive analysis. The validation of Android media shows that the media is suitable for use with an average of 72, practicality testing shows the ease of the learning process with an average of 94, effectiveness testing before using Android media is 32 and after using Android media is 87. The conclusion is that the Android media developed is valid, practical, and effective and can be used for the learning process. Furthermore, tests can be carried out on a wider scale to obtain more homogeneous data.